2018
DOI: 10.1039/c7tb02244a
|View full text |Cite
|
Sign up to set email alerts
|

The influence of bubble size on chondrogenic differentiation of adipose-derived stem cells in gelatin microbubble scaffolds

Abstract: In human bodies, cartilage tissue lacks the ability to heal when it encounters trauma or lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Similarly, other groups developed the microfluidic apparatus based on flow‐focusing technology for scaffold preparation (Wang et al, ). In addition to the differences in liquid flow rate, air pressure, gelatin and surfactant concentrations, the major improvement in our study is the collection device for the gelatin bubbles (Wu et al, ). We used the silicon wafer with a polydimethylsiloxane mold which is fabricated by soft lithography for bubble collection, and a scaffold with more compact structure can be prepared (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, other groups developed the microfluidic apparatus based on flow‐focusing technology for scaffold preparation (Wang et al, ). In addition to the differences in liquid flow rate, air pressure, gelatin and surfactant concentrations, the major improvement in our study is the collection device for the gelatin bubbles (Wu et al, ). We used the silicon wafer with a polydimethylsiloxane mold which is fabricated by soft lithography for bubble collection, and a scaffold with more compact structure can be prepared (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…A polydimethylsiloxane‐based (Sil‐More Industrial Ltd., Taipei, Taiwan) microfluidic device was used to fabricate the 3D gelatin bubble‐based scaffolds (Wu, Mei, Lin, Yang, & Yu, ). Each microfluidic channel houses an input for liquid component and gas, as well as an outflow for gelatin microbubbles (Figure ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the treatment of cartilage defects, the differentiation of stem cells into chondrocytes is an important cue [ 81 ]. Many physical and mechanical characteristics of the ECM, such as hypoxia, stiffness, topography, and pore size, are closely related to the interdifferentiation process of chondrocytes and stem cells [ 82 ].…”
Section: New Discoveries About Cancer and Other Diseases Based Onmentioning
confidence: 99%
“…Many physical and mechanical characteristics of the ECM, such as hypoxia, stiffness, topography, and pore size, are closely related to the interdifferentiation process of chondrocytes and stem cells [ 82 ]. Kuan-Han Wu et al [ 81 ] used gelatin as ECM in a microfabrication process to create a scaffold with different sizes of microbubbles and pores. They found that the size of microbubbles and pores can impact chondrogenesis, and a larger pore size is required for inducing mature chondrogenesis.…”
Section: New Discoveries About Cancer and Other Diseases Based Onmentioning
confidence: 99%